Unequal before the Law : Measuring Legal Gender Disparities across the World - Iqbal, Sarah (World Bank, Washington, DC, 2016)
Several economies have laws that treat women differently from men. This study explores the degree of such legal gender disparities across 167 economies around the world. This is achieved by constructing a simple measure of legal gender disparities to evaluate how countries perform. The average number of overall legal gender disparities across 167 economies is 17, ranging from a minimum of 2 to a maximum of 44. The maximum possible legal gender disparities is 71. The measure is found to be correlated with other measures of gender inequality, implying the measure does capture gender inequality while also differing from preexisting measures of gender inequality. A high degree of legal gender disparities is found to be negatively associated with a wide range of outcomes, including years of education of women relative to men, labor force participation rates of women relative to men, proportion of women top managers, proportion of women in parliament, percentage of women that borrowed from a financial institution relative to men, and child mortality rates. Subcategories within the legal disparities measure help to uncover specific types of legal disparities across economies.